Business Analysis And Entrepreneurial Strategies In The Coffee Powder Industry In Kepahiang Regency, Bengkulu Province (Case Study: Ck3 Coffee - Central Kedai Kopi Kepahiang) - Gustika, Soni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the business and entrepreneurial strategies implemented by Central Kedai Kopi Kepahiang (CK3) in the ground coffee industry in Kepahiang Regency, Bengkulu Province. CK3 is a coffee business founded by Panca Dewanto in Tebat Monok Village, Agrodehasen Rest Area, Bengkulu. With sales volume reaching 2,000 cups of coffee per month and hundreds of kilograms of coffee powder per month, CK3 has demonstrated significant growth in the local coffee industry. This study employs a qualitative approach using the case study method. Data collection was conducted through in-depth interviews with the founder, participatory observation, and document analysis. The analytical framework utilized the Business Model Canvas (Osterwalder & Pigneur, 2010), Porter’s Generic Strategies (Porter, 1985), and Entrepreneurial Orientation (Lumpkin & Dess, 1996). The results indicate that CK3 implements a differentiation strategy, focusing on the unique quality of Kepahiang Robusta coffee beans, a strategic location at a rest area, and a personalized consumer experience. The dominant dimensions of entrepreneurial orientation are proactiveness and innovativeness in product development. Effective marketing strategies include local market penetration, digital channel development, and building a community of coffee enthusiasts.